Burrow forms, growth rates and feeding rates of wood-boring Xylophagaidae bivalves revealed by micro-computed tomography - Amon, Diva J.; Sykes, Daniel; Ahmed, Farah; Copley, Jonathan T.; Kemp, Kirsty M.; Tyler, Paul A.; Young, Craig M.; Glover, Adrian G. (Frontiers in Marine Science, 2015)
Wood sinking into the deep sea is often colonized by species of the bivalve subfamily Xylophagaidae; specialist organisms that bore into it and digest cellulose with the aid of symbiotic bacteria. Very little is known about the nature of Xylophagaidae borings, Xylophagaidae abundances and population size structures, their rates of growth and their consumption rates of wood. To investigate this, several sets of experimental wood packages were deployed and retrieved: two sets from two seamount sites on the Southwest Indian Ridge (732-750 m), one from the Mid-Cayman Spreading Centre in the Caribbean (4773 m), and three sets from 500 m in the Tongue of the Ocean, Bahamas. The wood samples were scanned using X-ray micro-computed tomography (micro-CT). The wood at each deployment site was colonized by a different species of xylophagaid. Making novel use of micro-CT images, the morphology of intact xylophagaid borings were shown to resemble Prince Rupert’s Drops with ‘drop lengths’ varying between species. Mean sizes of Xylophagaidae and mean minimum growth rates (2.55 to 8.76 mm yr-1) varied among species also. Rates of wood degradation were up to 60 cm3 per year per 100 individuals but in reality, this may have been an underestimate. This analysis has given insight into the importance of the subfamily Xylophagaidae with regard to wood remineralization in the deep sea.